Disulfidptosis-related gene SLC3A2: a novel prognostic biomarker in nasopharyngeal carcinoma and head and neck squamous cell carcinoma - Zhang, Xinyi; Lin, Yiqi; Shi, Liang; Zhai, Aixia; Wu, Chao; Zhu, Qian-Ying (Frontiers in Oncology, 2025)
IntroductionNasopharyngeal carcinoma (NPC), one of the most common malignancies of the head and neck, is characterised by a complex pathogenesis and an unfavourable prognosis. Recently, disulfidoptosis, a novel form of cell death, has been proposed. Several studies in recent years have extensively investigated the function of the disulfidoptosis-related SLC7A11 gene in cancer, but the role of its partner protein, SLC3A2, remains unknown unclear in NPC.MethodsGEO database analysis confirmed SLC3A2's prognostic impact on nasopharyngeal carcinoma. ROC, Kaplan-Meier analyses, and stage-specific expression studies showed a strong correlation with poor HNSC prognosis. GO and KEGG analyses pinpointed relevant signaling pathways. In vitro, SLC3A2's influence on cell proliferation, migration, and invasion was evaluated through CCK8, wound healing, colony formation, transwell assays, and cell cycle analysis.ResultsIn this study, we identified the high expression of SLC3A2 in NPC and head and neck squamous cell carcinoma (HNSC) and analyzed its potential mechanism and correlation with patient prognosis. Furthermore, a negative relationship was found between the expression level of SLC3A2 and the extent of immune cell infiltration and immune checkpoint. Differentially expressed genes (DEGs) between the high and low SLC3A2 expression groups were primarily involved in cytokine-cytokine receptor interaction and immune response. Finally, in vitro experiments demonstrated that SLC3A2 stimulates tumor cell proliferation and migration. DiscussionIn conclusion, these results indicated a strong association between SLC3A2 and progression in both NPC and HNSC, suggesting it as a promising biomarker for predicting adverse prognosis in NPC and HNSC patients.